Resting-State Cortical Connectivity Underlying Cognitive-Motor Interactions in Gait and Postural Tasks in Young Adults. (4th January 2022) - Morelli, Nathan; Johnson, Nathan; Kaiser, Kimberly; Andreatta, Richard; Heebner, Nicholas; Hoch, Matthew
Abstract : Objective: The purpose of this study is to determine the relationship between intra- and internetwork connectivity and DTC of postural, gait, and cognitive performance in healthy, young adults. Background: Dual-task (DT) deficits persist after return to activity in those recovering from a sports related concussion. However, little is known about the relationship of cortical network function to DT capacity. Current evidence regarding the relationship between network connectivity and dual-task balance and gait performance is limited by focusing on older adults and those with cognitive impairments, using a condensed set of task demands, and neglecting the role of connectivity in the ability to adapt to minimize DT cost (DTC). Design/Methods: Twelve adults (7 females; age: 23.41 ± 2.74 years; height: 1.73 ± 0.10 m; weight: 72.66 ± 11.25 kg) volunteered for this study. Participants completed resting-state functional magnetic resonance imaging, as well as single and DT variants of the Concussion Balance Test, Sensory Organization Test, and gait. Functional connectivity within and between the default mode (DMN), salience (SAL), and sensorimotor (SMN) networks were calculated for all subjects. Pearson's correlations were used to assess the association of connectivity to balance and gait speed DTC. Results: Inter-network connectivity between to DMN to the SAL and SMN demonstrated moderate to strong association to DTC of gait speed and postural control during tasks which perturbed sensory environments (r = −0.59 to 0.94, p < 0.05). There was no relationship between connectivity and DTC of cognitive performance during DT (r = −0.50 to 0.54, p > 0.05). Conclusions: Our findings highlight the role of the SAL, SMN, and DMN in cognitive-motor interactions during gait and postural control. Furthermore, functional connectivity underlying DT gait and static postural control performance express inverse relationships, suggesting task-dependent differences in system level processing.